Olive Leaf Mottling Virus: A New Member of the Genus Olivavirus - Ruiz-García, Ana B.; Candresse, Thierry; Malagón, José; Ruiz-Torres, Manuel; Paz, Sergio; Pérez-Sierra, Ana; Olmos, Antonio (MDPI, 2024)
Studies of the virome of olive trees with symptoms of leaf mottling by high-throughput sequencing (HTS) revealed the presence of a new virus. Full coding genome sequences of two isolates were determined and consisted of a single RNA segment of 16,516 nt and 16,489, respectively. The genomic organization contained 10 open reading frames (ORFs) from 5′ to 3′ : ORF1a, ORF1b (RdRp), ORF2 (p22), ORF3 (p7), ORF4 (HSP70h), ORF5 (HSP90h), ORF6 (CP), ORF7 (p19), ORF8 (p12), ORF9 (p23) and ORF10 (p9). Phylogenetic analyses clustered this virus in the genus Olivavirus, family Closteroviridae, with the closest species being Olivavirus flaviolae, commonly named olive leaf yellowing-associated virus (OLYaV). However, amino acid sequences of all taxonomically relevant proteins showed, in all cases, a divergence higher than 25% between OLYaV and the new virus, indicating that it represents a new species in the genus Olivavirus for which the common name of olive leaf mottling virus (OLMV) is proposed. This study represents an advance in the genus Olivavirus and provides new insights into the olive virome.